2013
DOI: 10.1016/j.biocel.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin contributes to slow oxidative muscle fiber specification via PGC-1α and AMPK activation

Abstract: Erythropoietin activity, required for erythropoiesis, is not restricted to the erythroid lineage. In light of reports on the metabolic effects of erythropoietin, we examined the effect of erythropoietin signaling on skeletal muscle fiber type development. Skeletal muscles that are rich in slow twitch fibers are associated with increased mitochondrial oxidative activity and corresponding expression of related genes compared to muscle rich in fast twitch fibers. Although erythropoietin receptor is expressed on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 39 publications
5
43
0
Order By: Relevance
“…It is likely that EPO stimulation causes a rapid calcium influx and increased calcium influx may activate CaMKK activity, leading to increased AMPK activity. Also, our finding that AMPK mediates EPO activity in modulating redox status and regulating energy metabolic activity in adipocytes expands the relationship between EPO signaling and AMPK activity to multiple tissues in addition to our previously revealed skeletal muscle (Wang et al, 2013a) and suggests a possibly widespread involvement of EPO in AMPK mediated energy sensing network.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is likely that EPO stimulation causes a rapid calcium influx and increased calcium influx may activate CaMKK activity, leading to increased AMPK activity. Also, our finding that AMPK mediates EPO activity in modulating redox status and regulating energy metabolic activity in adipocytes expands the relationship between EPO signaling and AMPK activity to multiple tissues in addition to our previously revealed skeletal muscle (Wang et al, 2013a) and suggests a possibly widespread involvement of EPO in AMPK mediated energy sensing network.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, AMPK also regulates Sirt1, another metabolic sensor and a Nicotinamide adenine dinucleotide (NAD + ) dependent type III deacetylase sirtuin, that activates PGC-1α and various substrates including PPARγ (Canto and Auwerx, 2009; Canto et al, 2009). We previously demonstrated that EPO enhances AMPK activity in C2C12 myoblasts, which may mediates the EPO effect to promote slow muscle fiber specification (Wang et al, 2013a). EPO is also reported to trigger AMPK activity, leading to enhanced phosphorylation of β common receptor (βCR) and endothelial nitric oxide synthase (eNOS) to stimulate NO production and, ultimately, angiogenesis (Su et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PPAR␥ and C/EBPs are master regulators of adipogenesis. As a sensor of energy, AMPK has been shown to reduce fat accumulation and increase glucose tolerance, insulin sensitivity, and mitochondrial biogenesis (42)(43)(44)(45)(46)(47). The AMPK activator AICAR can inhibit 3T3-L1 adipocyte differentiation by blocking the expression of C/EBP␣ and PPAR␥ (36).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, only skeletal muscle myoblasts but not matured myotubes were found to show proliferative response to EPO stimulation (Figure 1). Further expression evidence demonstrated that EpoR is only expressed in muscle myoblasts and decreased with the skeletal muscle differentiation and no EPO response was detected in mature muscle fibers 12, 36. EPO stimulation in myoblasts promoted EpoR expression and muscle specific transcription factors, such as Myf5 and MyoD 14, 36.…”
Section: Epo/epor In Skeletal Musclementioning
confidence: 99%
“…The important metabolism sensors, AMPK and PGC-1α, which also are demonstrated to promote the slow and oxidative fiber specification 79, 80, were activated by EPO in the muscle 12. In comparison, skeletal muscle from wild type mice and mice with erythropoietin activity restricted to erythroid tissue has fewer slow twitch myofibers and reduced mitochondrial activity compared to the mice with overexpressed EPO 12. These observations suggest that EPO contributes to skeletal muscle fiber programming and metabolism, which may link EPO activity to the potential of anti-obesity and metabolism disorder.…”
Section: Epo/epor In Skeletal Musclementioning
confidence: 99%